Which healthcare workers work with acute respiratory illness? Evidence from Canadian acute-care hospitals during 4 influenza seasons: 2010–2011 to 2013–2014. (August 2019) - Jiang, Lili; McGeer, Allison; McNeil, Shelly; Katz, Kevin; Loeb, Mark; Muller, Matthew P.; Simor, Andrew; Powis, Jeff; Kohler, Philipp; Di Bella, Julia M.; Coleman, Brenda L.
Abstract: Background: Healthcare workers (HCWs) are at risk of acquiring and transmitting respiratory viruses while working in healthcare settings. Objectives: To investigate the incidence of and factors associated with HCWs working during an acute respiratory illness (ARI). Methods: HCWs from 9 Canadian hospitals were prospectively enrolled in active surveillance for ARI during the 2010–2011 to 2013–2014 influenza seasons. Daily illness diaries during ARI episodes collected information on symptoms and work attendance. Results: At least 1 ARI episode was reported by 50.4% of participants each study season. Overall, 94.6% of ill individuals reported working at least 1 day while symptomatic, resulting in an estimated 1.9 days of working while symptomatic and 0.5 days of absence during an ARI per participant season. In multivariable analysis, the adjusted relative risk of working while symptomatic was higher for physicians and lower for nurses relative to other HCWs. Participants were more likely to work if symptoms were less severe and on the illness onset date compared to subsequent days. The most cited reason for working while symptomatic was that symptoms were mild and the HCW felt well enough to work (67%). Participants were more likely to state that they could not afford to stay home if they did not have paid sick leave and were younger. Conclusions: HCWs worked during most episodes of ARI, most often because their symptoms were mild. Further data are needed to understand how best to balance the costs and risks of absenteeism versus those associated with working while ill.